مفهوم الشفاعة الأخروية عند الإمام الزمخشري في تفسيره : دراسة تحليلية - Lukmanul Hakim (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This research studies the concept of intercession (Shafi'ah) in the hereafter according to al-Imam al-Zamakhshari in his Qur'anic commentary, explains evidences and discusses them intellectually through al-kashshaf 'an haqaiq ghawamidh al-tanzil wa 'uyun al-aqawil fi wujuh al-ta'wil. This research is based on inductive approach through the study of related Qur'anic verses in the subject of intercession in the hereafter, while taking into consideration, other relevant Qur'anic commentaries and sound ahadith. It also looks into all other verses related to intercession in the hereafter. The research uses analytical method to analyse and study information contained on this issue and states the position of al-Imam al-Zamakhshari in his al-kashshaf. Among the most important findings of the researcher is that al-Imm al-Zamakhshari believes that intercession in the hereafter mentioned in the Qur'an raises the grades and increases the rewards of the believers. However, those with major sins shall be in hell fire and will abide therein forever. This is contrary to the doctrine of the ahl al-Sunnah wa al-Jama'ah who believe that intercession in the hereafter is possible for major sinners among the believers (Oneness of Allah).